8-Hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material and preparation method thereof
By developing 8-hydroxyquinoline multi-core tin oxygen cluster crystal luminescent materials, using metal salt regulation strategies and hydrothermal reaction methods, the problem of insufficient research on multi-karyotype and tin-based complexes in the existing technology has been solved, and the efficient synthesis of the material and excellent luminescent performance have been achieved.
Patent Information
- Application Number
- CN202310300179.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-03-27
AI Technical Summary
In the prior art, the research on 8-hydroxyquinoline metal organic complexes is relatively single, especially the research on polykaryotic and tin-based complexes is less, resulting in limited structural controllability and luminous performance optimization.
Three 8-hydroxyquinoline multi-nuclear tin oxygen cluster crystal luminescent materials were developed, including Compound 1, Compound 2 and Compound 3. Materials with precise structural information, high fluorescence lifetime and quantum yield were prepared through specific metal salt regulation strategies and hydrothermal reaction methods.
It realizes efficient synthesis of materials, has excellent electron transport performance, fluorescence efficiency, stability and solubility, and is suitable for electroluminescence and EUV lithography.
Smart Images

Figure CN116333727B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic chemistry or material chemistry, and specifically relates to an 8-hydroxyquinoline type multi-core tin oxide cluster crystalline luminescent material and a preparation method thereof. Background Art
[0002] Organic electroluminescence (OLED for short) refers to the phenomenon that organic materials emit light under the stimulation of electric current or electric field. At present, the research on OLED at home and abroad is mainly focused on luminescent materials, device manufacturing and product development. Related research is no longer limited to academia. Almost all internationally renowned electronics companies and chemical companies have invested huge manpower, material and financial resources in this research field and have made great progress. The number of related monographs and patents increases by hundreds every year, and various materials with excellent performance continue to appear, which greatly accelerates the industrialization process of OLED.
[0003] In 1987, 8-hydroxyquinoline aluminum (Alq 3 ) as the light-emitting layer of the electroluminescent device, the driving voltage is less than 10V, and the luminous brightness reaches 1000Cd / m 2 , and the service life is 100h. Since then, researchers have begun to realize the broad application prospects and value of 8-hydroxyquinoline metal complexes (8HQM) in the field of organic electroluminescence, and have begun to invest a lot of energy in its research.
[0004] 8-Hydroxyquinoline metal complexes are a very typical organic electroluminescent material with good stability, electron transport performance and fluorescence efficiency. Its derivatives also show excellent electroluminescent properties, and have great value and wide application in energy-saving lighting, color-changing devices, and especially wireless communication tools. In addition, this type of compound also has good impact resistance and vibration resistance, so it is widely used in active display or backlight display devices such as car dashboards, audio and TV remote controls, handheld GPS receivers, and portable computers.
[0005] At present, there are many studies on mononuclear 8-hydroxyquinoline metal-organic complexes, while the research on multinuclear 8-hydroxyquinoline functional metal-organic complexes is still insufficient, and the research on 8-hydroxyquinoline tin-based complexes is even less. Combined with the many advantages of tin oxide clusters (accurate atomic position information, clear ligand-cluster core connection mode and adjustable cluster core size, etc.), in-depth research on the influence of metal core number, nuclear structure, spatial structure and even guest molecules on its luminescence properties can be carried out to control the luminescence spectrum of 8-hydroxyquinoline metal complexes, thereby further optimizing its luminescence properties, which has important practical application value for expanding the application range of organic electroluminescent materials and optimizing the performance of devices. However, the unclear formation mechanism and Mq of tin oxide clusters are still unclear. nThe mononuclear metal-organic complexes limit or even hinder the development of new 8-hydroxyquinoline-based metal-organic materials with controllable structures and good luminescence properties.
[0006] Therefore, developing new synthetic methods and strategies to obtain polynuclear 8-hydroxyquinoline-based metal organic complexes with unique structures and tunable optical properties is a huge challenge facing chemists today. Summary of the invention
[0007] In order to solve the above technical problems, further develop and optimize new materials, the present invention discloses three examples of 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent materials with accurate structural information, high fluorescence lifetime and quantum yield, high hydrophobicity, good stability and solubility, and is expected to be used as a new type of luminescent tin oxide cluster material in the field of electroluminescence and EUV photoresist. The method of the present invention has easy-to-obtain raw materials, a simple preparation method, high yield, is suitable for large-scale synthesis, and can achieve low cost and high efficiency.
[0008] First, the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material of the present invention comprises the following compounds: (8-Q 1 8-Hydroxyquinoline; 8-Q 2 =8-hydroxy-2-methylquinoline)
[0009] Compound 1: Molecular formula [(BuSn) 10 (8-Q 1 ) 6 (μ 2 -OH) 2 (μ 3 -O) 11 ]·H 2 O.CH 3 CN(Sn 10 ), crystallographic data α=90°, β=100.549(2)°, γ=90°, Z=4, monoclinic system, P2 1 / n space group;
[0010] Compound 2: Molecular formula [(BuSn) 12 (O) 13 (OH) 4 (8-Q 1 ) 3 (CH 3 COO 3 ]·H 2 O(Sn 12 ), crystallographic data α=90°, β=93.7920(10)°, γ=90°, Z=4, monoclinic system, P2 1 / n space group;
[0011] Compound 3: Molecular formula [(BuSn) 12 (O) 13 (OH) 4 (8-Q 2 ) 3 (CH 3 COO 3 ]·H 2 O·3CH 3 CN(Sn 12 -Me), the crystallographic data are α=82.1576(12)°, β=80.6499(11)°, γ=67.7108(11)°, Z=4, monoclinic system, Cc space group.
[0012] Furthermore, in the above technical solution, in the compound 1, the entire molecular skeleton structure is an "ear protection cap" type, comprising 10 butyl Sn IV ions. Among them, 6 butyltin ions are coordinated with 6 deprotonated 8-hydroxyquinoline N,O atoms, and a "cap" is constructed through bridging oxygen atoms. The 4 butyltin ions are connected to each other through bridging oxygen atoms to form a "cap top", which contains a common O-terminated {Sn 3} and a five-coordinated butyltin ion. The "cap circumference" and "cap top" are connected by μ 3 -O combines them together.
[0013] Furthermore, in the above technical solution, in the compounds 2 and 3, the entire molecular skeleton structure presents a new "cage" structure, which is divided into three parts: "poles" and "equator", and contains 12 butyltin ions. IV ions, which are common O-terminated tin trimers, are arranged in the same direction (different from the reported cage-type Sn 12 Sn 3} "back-to-back" arrangement mode). The end cap O faces the outside of the "cage" {Sn 3} coordinated with three deprotonated acetic acids, while the terminal O is inside the "cage" {Sn 3}, its 3 μ 2 -O points to the outside of the "cage". The six butyltin ions at the "equator" are connected alternately by single oxygen bridges and double oxygen bridges, of which three alternate butyltin ions are coordinated with three deprotonated 8-hydroxyquinoline or 8-hydroxy-2-methylquinoline N, O. The "poles" are connected to the "equator" through μ 3 -O combines them together.
[0014] Secondly, the present invention also provides a method for preparing the above-mentioned 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material, comprising the following operations:
[0015] A. Mix 8-hydroxyquinoline compounds, metal salts, butyl stannoic acid and acetonitrile evenly, add them into a high-pressure reactor, and react at 65-80°C;
[0016] B. Filter the mixture after the reaction in step A to obtain green (green octahedral / yellow-green columnar) crystals; then wash with acetonitrile, filter, and dry at room temperature to obtain Sn 10 / Sn 12 Type crystalline luminescent tin-oxygen clusters.
[0017] Further, in the above technical solution, the 8-hydroxyquinoline compound is selected from 8-hydroxyquinoline or 8-hydroxy-2-methylquinoline; the metal salt is selected from sodium methoxide, sodium formate, ferrous acetate, chromium acetate, silver acetate or zinc acetate. Under preferred conditions, for 8-hydroxyquinoline, the metal salt is sodium methoxide, sodium formate, ferrous acetate, chromium acetate, silver acetate or zinc acetate; for 8-hydroxy-2-methylquinoline, the metal salt is ferrous acetate, chromium acetate, silver acetate or zinc acetate.
[0018] Furthermore, in the above technical solution, the molar ratio of the 8-hydroxyquinoline compound, the metal salt and the butyl stannoic acid is 0.5-1.5:0.05-0.5:0.5-2.
[0019] Furthermore, in the above technical solution, the reaction temperature is 65-80°C; and the reaction time is 2-5 days.
[0020] Thirdly, the present invention also provides possible applications of the above-mentioned 8-hydroxyquinoline-based multi-nuclear tin oxide cluster crystalline luminescent material in the fields of electroluminescence and EUV lithography.
[0021] Beneficial effects of the invention:
[0022] Compared with existing luminescent materials and key materials of photoresists, the present invention is a crystalline luminescent material of 8-hydroxyquinoline multi-core tin oxide clusters. As a luminescent material, it has excellent performance in performance indicators such as electron transport performance, fluorescence efficiency, stability, and film quality. It is not only an electroluminescent material, but also an excellent electron transporter. As a tin oxide nanocluster, it can provide optimal EUV absorption and reduce photon shot noise, thereby improving pattern resolution. Its structural block size is only a small part of that of traditional polymer-based resists, and can be adjusted to absorb EUV photons in the best way. Combined with Sn as the working medium of extreme ultraviolet light source, tin oxide nanocluster will become a star material in the research of EUV lithography technology. The crystal structure of this type of material, the entire molecular skeleton structure of compound 1 is an "ear cap" type, containing 10 butyl Sn IVions. Among them, 6 butyltin ions are coordinated with 6 deprotonated 8-hydroxyquinoline N,O atoms, and a "cap" is constructed through bridging oxygen atoms. The 4 butyltin ions are connected to each other through bridging oxygen atoms to form a "cap top", which contains a common O-terminated {Sn 3} and a five-coordinated butyltin ion. The "cap circumference" and "cap top" are connected by μ 3 -O are combined together. The entire molecular skeleton structure of compounds 2 and 3 presents a new "cage" structure, which is divided into three parts: the "poles" and the "equator", containing 12 butyltin ions. There are 3 butyltin ions at each of the "poles". IV ions, which are common O-terminated tin trimers, are arranged in the same direction, which is different from the reported cage-type Sn 12 {Sn 3 In addition, the end cap O faces the outside of the cage {Sn 3} coordinated with three deprotonated acetic acids, while the terminal O is inside the "cage" {Sn 3}, its 3 μ 2 -O points to the outside of the "cage". The six butyltin ions at the "equator" are connected alternately by single oxygen bridges and double oxygen bridges, of which three alternate butyltin ions are coordinated with three deprotonated 8-hydroxyquinoline or 8-hydroxy-2-methylquinoline N, O. The "poles" are connected to the "equator" through μ 3 -O are combined together. The fluorescence spectrum and fluorescence decay spectrum show that the maximum emission wavelengths of these three materials are 526nm, 504nm and 498nm, respectively, which belong to the green light emission range; the fluorescence lifetimes are 11.40ns, 18.78ns and 18.19ns, respectively, and the quantum yields are 15.43%, 98.64% and 73.13%, respectively. In addition, the thermogravimetric spectrum shows that these three materials remain stable below 220°C, and in the specific application process, the implementation conditions are relatively easy to achieve. This type of material has the advantages of both good stability of inorganic substances and high fluorescence quantum efficiency of organic substances, and is one of the luminescent materials with the broadest application prospects.
[0023] The present invention has found in the synthesis that the metal salt regulation strategy is very effective for the formation of the novel 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material. The present invention provides an organic-inorganic hybrid material that can be used for electroluminescence and EUV photoresist, seeks to design a material with accurate structural information, high fluorescence quantum yield, high hydrophobicity, good stability, and readily available raw materials, simple preparation method, high yield, and large-scale synthesis of tin oxide clusters.
[0024] Different from the reported tin oxide clusters, the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material of the present invention has mild reaction conditions, convenient operation, good feasibility, simple and easy-to-obtain raw materials, high yield, and is suitable for one-pot large-scale synthesis. In terms of properties, it has good thermal stability, easy solubility, high fluorescence lifetime and quantum yield, and is a highly potential excellent luminescent material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 , Fig. 9 , Fig.17 They are respectively the crystal structure diagrams of the 8-hydroxyquinoline type multi-core tin oxide cluster crystalline luminescent materials in Examples 1, 2 and 3 of the present invention;
[0026] Figure 2 , Fig.10 , Fig.18 They are respectively the luminescence images of the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent materials in Examples 1, 2 and 3 of the present invention before and after irradiation with 365 nm light;
[0027] Figure 3 , Fig.11 , Fig.19 They are crystal photos and large-scale synthesis diagrams of 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent materials in Examples 1, 2 and 3 of the present invention respectively;
[0028] Figure 4 , Fig.12 , Fig. 20 They are respectively the powder X-ray diffraction patterns of the large-scale synthesis of 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent materials in Examples 1, 2 and 3 of the present invention;
[0029] Figure 5 , Fig.13 , Fig.21 They are respectively the UV-visible diffuse reflectance spectra of the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent materials in Examples 1, 2 and 3 of the present invention;
[0030] Figure 6 , Fig.14 , Fig. 22 They are the photoluminescence spectra of the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent materials in Examples 1, 2 and 3 of the present invention respectively;
[0031] Figure 7 , Fig.15 , Fig.23 They are respectively the fluorescence decay spectra of the 8-hydroxyquinoline type multi-core tin oxide cluster crystalline luminescent materials in Examples 1, 2 and 3 of the present invention;
[0032] Figure 8 , Fig.16 , Fig.24 They are the thermogravimetric spectra of the 8-hydroxyquinoline type multi-nuclear tin oxide cluster crystalline luminescent materials in Examples 1, 2 and 3 of the present invention respectively. DETAILED DESCRIPTION
[0033] The present invention will be further described below by way of embodiments in conjunction with the accompanying drawings.
[0034] The metal salt control strategy adopted in this embodiment is a simple and effective method for synthesizing 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent materials. The screening basis and process of the reaction conditions are as follows:
[0035] 1. Tin source selection
[0036] Considering the hydrolysis rate of tin sources, inorganic tin sources such as SnCl 4 ·5H 2 O, etc., due to their rapid and difficult-to-control hydrolysis, are usually not conducive to the formation of tin oxide clusters and their structural diversity; while organic tin sources such as butyl stannic acid, dibutyl tin dichloride, and triphenyltin chloride have slow hydrolysis rates, which are conducive to the coordination reaction, thereby realizing the assembly, modification and regulation of the tin oxide cluster structure.
[0037] From the perspective of the reactivity of the tin source, since the Sn-C bond in alkyltin (IV) is stable and not easy to break, di- and tri-organotin have fewer coordination sites, while mono-organotin such as butyl stannic acid has relatively more coordination sites, which is conducive to the formation of tin oxide clusters with diverse structures through coordination reactions.
[0038] Therefore, butyl stannoic acid was selected as the single organotin source for the synthesis of the target tin oxo cluster.
[0039] 2. Ligand selection
[0040] The ligand structure is one of the most important structural guiding factors affecting the self-assembly of tin oxide clusters. On the one hand, 8-hydroxyquinoline and its derivatives have obvious structural advantages: 1) 8-hydroxyquinoline is a nitrogen heterocyclic compound containing a conjugated fused ring structure, which is a good metal ion chelator and can coordinate with most metals to form 8-hydroxyquinoline metal-organic complexes with different structures; 2) The skeleton of 8-hydroxyquinoline can be appropriately functionally modified at multiple sites, thereby effectively changing the energy level difference between HOMO and LUMO of 8-hydroxyquinoline to achieve the purpose of regulating its luminescence wavelength. On the other hand, 8-hydroxyquinoline compounds are widely used to prepare metal-organic complex luminescent materials and study their fluorescence and organic electroluminescent device performance due to their large absorption coefficient and strong coordination ability. In addition, the electronic effect of the substituent can effectively regulate the optical properties of 8-hydroxyquinoline ligands and the complexes assembled by the ligands, including fluorescence lifetime, maximum emission wavelength, and quantum yield. Therefore, 8-hydroxyquinoline compounds are one of the most important ligand sources for the formation of metal-organic functional complexes. Various 8-hydroxyquinoline derivatives were tried to screen suitable ligands and their ratios to metal sources, as follows:
[0041]
[0042] 3. Metal salt selection
[0043] The characteristics of metal ions play an important role in the assembly process of tin oxide clusters, which not only cause changes in their nuclear number and spatial size, but also may lead to changes in supramolecular structure and the formation of new topological structures. On the one hand, the anions and cations in metal salts can induce the coordination and aggregation of tin ions into tin oxide clusters with diverse configurations or heterometallic doped tin oxide clusters through templated effects. On the other hand, their anions can also participate in coordination reactions to construct new functional tin oxide clusters. Here, other reaction conditions are fixed and a variety of metal salts are tried to screen suitable metal salts, as follows:
[0044]
[0045] 4. Determination of reaction temperature and time
[0046] The conditions for the formation of tin oxide clusters are relatively mild, with a temperature generally between 60 and 120°C and a time of 2 to 5 days. The optimal temperature and time required for the reaction were screened through specific experimental implementation (with a certain ratio of reactants), and the results are as follows:
[0047]
[0048] In summary, the optimal synthesis schemes for three 8-hydroxyquinoline-based multi-nuclear tin oxide cluster crystalline luminescent materials were determined, namely, the tin source was butylstannic acid; the ligands were 8-hydroxyquinoline and 8-hydroxy-2-methylquinoline respectively; the metal salts were sodium formate, ferric acetate, and chromium acetate respectively; acetonitrile was used as the solvent, and the reaction was carried out at 80°C for 5 days.
[0049] Example 1
[0050] 1mmol 8-hydroxyquinoline, 0.37mmol sodium formate, 1mmol butyl stannic acid and 6mL acetonitrile solution were mixed evenly and loaded into a hydrothermal reactor, and reacted at 80°C for 5 days. The obtained mixture was filtered to obtain green strip crystals. The acetonitrile was washed, filtered, and dried at room temperature to obtain 8-hydroxyquinoline decadic tin oxide cluster crystalline luminescent material with a yield of 73% (based on butyl stannic acid).
[0051] The single crystal diffraction data analysis of the green strip crystals prepared in this example shows that the cluster molecular formula is [(BuSn) 10 (μ 3 -O) 11 (μ 2 -OH) 2 (8-Q 1 ) 6 ]·H 2 O.CH 3 CN, molecular weight is 2892.23, crystallographic data are α=90°, β=100.549(2)°, γ=90°, Z=4, monoclinic system, P2 1 / n space group. The crystal structure is Figure 1 As shown, the entire molecular skeleton structure is an "ear cap" type, containing 10 butyl Sn IV ions. Among them, 6 butyltin ions are coordinated with 6 deprotonated 8-hydroxyquinoline N,O atoms, and a "cap" is constructed through bridging oxygen atoms. The 4 butyltin ions are connected to each other through bridging oxygen atoms to form a "cap top", which contains a common O-terminated {Sn 3} and a five-coordinated butyltin ion. The "cap circumference" and "cap top" are connected by μ 3 -O combines them together.
[0052] The powder XRD test of the 8-hydroxyquinoline multi-core tin oxide cluster crystalline luminescent material prepared in this example is ( Figure 4 ) shows that the powder XRD results of the material of this embodiment at different synthesis scales are consistent with the single crystal simulation results, and all are pure phase materials, which are suitable for large-scale one-pot synthesis.
[0053] UV-Visible absorption and diffuse reflectance spectroscopy ( Figure 5) shows that the material of this embodiment has strong absorption at 273nm and 410nm, and its optical band gap value is about 2.60eV, indicating that the material is a potential photoelectric conversion material.
[0054] Photoluminescence spectrum and fluorescence decay spectrum ( Figure 6 and Figure 7 ) shows that the maximum emission peak of the material in this embodiment is located at 526nm, which belongs to the green light emission range; the fluorescence decay time is 11.40ns, and the quantum yield is 15.43%, indicating that the material is a potential green light emitting material.
[0055] Thermogravimetric test curve ( Figure 8 ) shows that the material of this embodiment remains basically stable within 220°C, loses weight rapidly by about 36% at 220-425°C, and then enters a slow weight loss stage.
[0056] Embodiment 2:
[0057] 1mmol 8-hydroxyquinoline, 0.103mmol ferric acetate, 1mmol butyl stannic acid and 6mL acetonitrile were mixed evenly and loaded into a hydrothermal reactor, and reacted at 80°C for 5 days. The obtained mixture was filtered to obtain green octahedral crystals. The acetonitrile was washed, filtered, and dried at room temperature to obtain 8-hydroxyquinoline type dodecanuclear tin oxide cluster crystalline luminescent material with a yield of 86% (based on ferric acetate).
[0058] The single crystal diffraction data analysis of the green octahedral crystals prepared in this example shows that the cluster molecular formula is [(BuSn) 12 (O) 13 (OH) 4 (8-Q 1 ) 3 (CH 3 COO 3 ]·H 2 O, molecular weight is 3013.51, crystallographic data is α=90°, β=93.7920(10)°, γ=90°, Z=4, monoclinic system, P2 1 / n space group. The crystal structure is Fig. 9 As shown in the figure, the entire molecular skeleton structure is a new type of "cage" structure, which is divided into three parts: the "poles" and the "equator", containing 12 butyltin ions. IV ions, which are common O-terminated tin trimers, are arranged in the same direction, which is different from the reported cage-type Sn 12 Sn 3 In addition, the end cap O faces the {Sn 3} is coordinated with three deprotonated acetic acids, while the terminal O is in the "cage" {Sn 3}, its 3 μ 2 -O points to the outside of the cage. The six butyltin ions at the equator are connected alternately by single oxygen bridges and double oxygen bridges, of which three alternating butyltin ions are coordinated with three deprotonated 8-hydroxyquinoline N,O. The two poles are connected to the equator through μ 3 -O combines them together.
[0059] The powder XRD test of the 8-hydroxyquinoline multi-core tin oxide cluster crystalline luminescent material prepared in this example is ( Fig.12 ) shows that the powder XRD results of the material of this embodiment at different synthesis scales are consistent with the single crystal simulation results, and all are pure phase materials, which are suitable for large-scale one-pot synthesis.
[0060] UV-Visible absorption and diffuse reflectance spectroscopy ( Fig.13 ) shows that the material of this embodiment has strong absorption at 270nm and 407nm, and its optical band gap value is about 2.65eV, indicating that the material is a potential photoelectric conversion material.
[0061] Photoluminescence spectrum and fluorescence decay spectrum ( Fig.14 and Fig.15 ) shows that the maximum emission peak of the material in this embodiment is located at 504nm, which belongs to the green light emission range; the fluorescence decay time is 18.78ns, and the quantum yield is 98.64%, indicating that the material is a potential excellent green light emitting material.
[0062] Thermogravimetric test curve ( Fig.16 ) shows that the material of this embodiment remains basically stable within 245°C, loses weight rapidly by about 27% at 245-410°C, has almost no mass loss at 410-570°C, and loses weight slowly by about 10% at 570-800°C.
[0063] Embodiment 3:
[0064] 1mmol 8-hydroxy-2-methylquinoline, 0.087mmol chromium acetate, 1mmol butyl stannic acid and 6mL acetonitrile were mixed evenly and loaded into a hydrothermal reactor, and reacted at 80°C for 5 days. The obtained mixture was filtered to obtain yellow-green columnar crystals. The acetonitrile was washed, filtered, and dried at room temperature to obtain 8-hydroxyquinoline type dodecanuclear tin oxide cluster crystalline luminescent material with a yield of 88% (based on chromium acetate).
[0065] The analysis of the single crystal diffraction data of the yellow-green columnar crystal prepared in this example shows that the cluster molecular formula is [(BuSn) 12 (O) 13 (OH) 4 (8-Q 2 )3 (CH 3 COO 3 ]·H 2 O·3CH 3 CN, molecular weight is 3178.7 5, crystallographic data are α=82.1576(12)°, β=80.6499(11)°, γ=67.7108(11)°, Z = 4, monoclinic system, Cc space group. The crystal structure is as follows Fig.17 As shown in the figure, the entire molecular skeleton structure is a new type of "cage" structure, which is divided into three parts: the "poles" and the "equator", containing 12 butyltin ions. IV ions, which are common O-terminated tin trimers, are arranged in the same direction, which is different from the reported cage-type Sn 12 Sn 3 In addition, the end cap O faces the outside of the cage {Sn 3} coordinated with three deprotonated acetic acids, while the terminal O is inside the "cage" {Sn 3}, its 3 μ 2 -O points to the outside of the "cage". The six butyltin ions at the "equator" are connected alternately by single oxygen bridges and double oxygen bridges, of which three alternate butyltin ions are coordinated with three deprotonated 8-hydroxy-2-methylquinoline N,O. The "poles" are connected to the "equator" through μ 3 -O combines them together.
[0066] The powder XRD test of the 8-hydroxyquinoline multi-core tin oxide cluster crystalline luminescent material prepared in this example is ( Fig. 20 ) shows that the powder XRD results of the material of this embodiment at different synthesis scales are consistent with the single crystal simulation results, and all are pure phase materials, which are suitable for large-scale one-pot synthesis.
[0067] UV-Visible absorption and diffuse reflectance spectroscopy ( Fig.21 ) shows that the material of this embodiment has strong absorption at 271nm and 398nm, and its optical band gap value is about 2.77eV, indicating that the material is a potential photoelectric conversion material.
[0068] Photoluminescence spectrum and fluorescence decay spectrum ( Fig. 22 and Fig.23 ) shows that the maximum emission peak of the material in this embodiment is located at 498nm, which belongs to the green light emission range; the fluorescence decay time is 18.19ns, and the quantum yield is 73.13%, indicating that the material is a potential and excellent green light emitting material.
[0069] Thermogravimetric test curve ( Fig.24) shows that the material of this embodiment remains basically stable within 220°C, loses weight rapidly by about 27% at 220-480°C, has almost no quality loss at 480-570°C, and loses weight slowly by about 10% at 570-800°C.
[0070] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. 8-Hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material, characterized in that: Selected from the following compounds: Compound 1: Molecular formula [(BuSn) 10 (8-Q 1 )6(μ2-OH)2(μ3-O) 11 ]·H2O·CH3CN, crystallographic data α=90°, β=100.549(2)°, γ=90°, Z = 4, monoclinic system, P21 / n space group; Compound 2: Molecular formula [(BuSn) 12 (O) 13 (OH)4(8-Q 1 )3(CH3COO)3]·H2O, crystallographic data α=90°, β=93.7920(10)°, γ=90°, Z = 4, monoclinic system, P21 / n space group; Compound 3: Molecular formula [(BuSn) 12 (O) 13 (OH)4(8-Q 2 )3(CH3COO)3]·H2O·3CH3CN, crystallographic data α=82.1576(12)°, β=80.6499(11)°, γ=67.7108(11)°, Z = 4, monoclinic system, Cc space group; Among them: 8-Q 1 8-Hydroxyquinoline; 8-Q 2 =8-hydroxy-2-methylquinoline.
2. The 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material according to claim 1, characterized in that: In compound 1, the entire molecular skeleton structure is an "ear cap" type, containing 10 butyl Sn IV ions; among them, 6 butyltin ions are coordinated with 6 deprotonated 8-hydroxyquinoline N,O, and a "cap ring" is constructed through bridging oxygen atoms. The 4 butyltin ions are connected to each other through bridging oxygen atoms to form a "cap top". The "cap top" contains 1 common O-terminated {Sn3} and 1 five-coordinated butyltin ion; the "cap ring" and the "cap top" are combined together with the help of μ3-O.
3. The 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material according to claim 1, characterized in that: In compounds 2 and 3, the entire molecular skeleton structure presents a new "cage" structure, which is divided into three parts: the "poles" and the "equator", containing 12 butyltin ions; each of the "poles" has 3 butyltin ions. IV The ion is a common O-terminated tin trimer, and the two are arranged in the same direction; the terminal O faces the outside of the "cage" {Sn3} and is coordinated with three deprotonated acetic acids, while the terminal O is inside the "cage" {Sn3}, and its three μ2-O points to the outside of the "cage"; the six butyltin ions at the "equator" are alternately connected by single oxygen bridges and double oxygen bridges, among which the three alternating butyltin ions are coordinated with three deprotonated 8-hydroxyquinoline or 8-hydroxy-2-methylquinoline N,O; the "poles" are respectively combined with the "equator" through μ3-O.
4. A method for preparing the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material according to claim 1, characterized in that: The method comprises the following steps: A. uniformly mixing 8-hydroxyquinoline compounds, metal salts, butyl stannic acid and acetonitrile, adding the mixture into a high pressure reactor, and reacting at 65-80° C.; B. filtering the mixture after the reaction in step A to obtain green crystals; Then wash with acetonitrile, filter, and dry at room temperature to obtain Sn 10 / Sn 12 Type crystalline luminescent tin-oxygen clusters.
5. The method for preparing the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material according to claim 4, characterized in that: The 8-hydroxyquinoline compound is selected from 8-hydroxyquinoline or 8-hydroxy-2-methylquinoline; the metal salt is selected from sodium methoxide, sodium formate, ferrous acetate, chromium acetate, silver acetate or zinc acetate.
6. The method for preparing the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material according to claim 5, characterized in that: The 8-hydroxyquinoline compound is selected from 8-hydroxyquinoline; the metal salt is selected from sodium methoxide, sodium formate, ferrous acetate, chromium acetate, silver acetate or zinc acetate.
7. The method for preparing the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material according to claim 5, characterized in that: The 8-hydroxyquinoline compound is selected from 8-hydroxy-2-methylquinoline; the metal salt is selected from ferric acetate, chromium acetate, silver acetate or zinc acetate.
8. The method for preparing the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material according to claim 4, characterized in that: The molar ratio of the 8-hydroxyquinoline compound, the metal salt and the butyl stannic acid is 0.5-1.5:0.05-0.5:0.5-2.
9. The method for preparing the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline luminescent material according to claim 4, characterized in that: The reaction time is 2-5 days.
10. Use of the 8-hydroxyquinoline polynuclear tin oxide cluster crystalline light-emitting material according to claim 1 in the fields of electroluminescent diodes and EUV lithography.
Citation Information
Patent Citations
Organotin-oxygen cluster containing ferrocene pyrazole and application of cluster
CN102093431A
Organic tin-inorganic tin hybrid Sn18 type crystalline tin-oxygen cluster compound and preparation method thereof
CN114167685A